DETECTION AND PATHOGENICITY LEVEL SCREENING OF HEMOLYTIC BACTERIA ISOLATED FROM UNPACKED CHICKEN NUGGET : Received: 04th October 2023 Revised: 13th October 2023, 02nd November 2023, 06th November 2023 Accepted: 08th November 2023 - Ika Alfiyani; Ana Hidayati Mukaromah; Muhammad Ardi Afriansyah; Stalis Norma Ethica (LIFE: International Journal of Health and Life-Sciences, 2023)
Food poisoning is a severe threat that can lead to death. According to the WHO, cases of food poisoning have been on the rise in recent years. Pathogenic bacteria are responsible for food poisoning, often originating from contaminated food. Chicken nuggets, a popular ready-to-eat food, are susceptible to bacterial growth due to the risk of microbial contamination during storage. This study aims to assess the pathogenicity levels of bacteria in chicken nuggets when stored at room temperature for seven days. Samples from chicken nuggets left at room temperature were diluted and cultured on Nutrient Agar (NA) media. Subsequently, bacterial pathogenicity screening was conducted using MacConkey Agar (MC), Blood Agar Plate (BAP), and Chocolate Agar Plate (CAP). The results revealed six bacterial isolates labeled FMCN-1 to FMCN-6 (FMCN denoting Fatmawati Market chicken nugget). Most isolates exhibited a moderate level of pathogenicity (FMCN-2, FMCN-3, FMCN-4, FMCN-5, and FMCN-6), with only one isolate demonstrating low pathogenicity (FMCN-1). In conclusion, storing chicken nuggets at room temperature for seven days can lead to bacterial contamination with mostly moderate pathogenicity. Further molecular analysis is required to identify the potentially harmful bacteria.